The integration of yoga in physical therapy clinical practice - Allie Thomas; Lindsey Kirschbaum; Brandi M. Crowe; Marieke Van Puymbroeck; Arlene A. Schmid (Elsevier, 2021)
Health professionals are beginning to use yoga as a treatment modality. However, evidence explaining physical therapists' integration of yoga in clinical practice is lacking. Objective: The purpose of this study was to explore how, why, and with whom physical therapists integrate yoga into clinical practice. Design: This study is a secondary analysis of qualitative data collected during a larger multi-methods study. Thematic analysis of 13 interviews was conducted. Results: Analysis indicated four themes, and six subthemes. Facilitating yoga in clinical practice and yoga training themes; including evaluation of outcomes, billing, terminology, and safety subthemes describe how physical therapists are using yoga in clinical practice. The perceived client outcomes theme, including physical and psychosocial outcomes explain why physical therapists use yoga in practice. The yoga with clinical populations theme addresses with whom physical therapists are using yoga. Conclusion: Physical therapists are using yoga with individuals with various health conditions to improve their physical and mental health. Findings support the need for physical therapists to increase their assessment and documentation of functional outcomes associated with client's yoga participation. Documentation could contribute to evidence-based literature related to how, why, and with whom physical therapists are using yoga. Documented outcomes could also provide rationale for yoga to receive classification as a reimbursable complementary and integrative health approach. Future research involving a larger, diverse sample (e.g., physical therapists with varying levels of education and yoga training) focused on how, why, and with whom physical therapists integrate yoga into clinical practice is recommended.